Compliant universal grippers as adaptive feet in legged robots. (3rd August 2018) - Hauser, S.; Mutlu, M.; Banzet, P.; Ijspeert, A.J.
ABSTRACT: This work investigates the usage of compliant universal grippers as a novel foot design for legged locomotion. The method of jamming of granular media in the universal grippers is characterized by having two distinct states: a soft, fluid-like state which in locomotion can be used to damp impact forces and enable passive shape adaptation especially on rough terrain, and a hard, solid-like state that is more suited to transmit propulsion forces. We propose a system that actively uses and switches between both states of a foot design based on granular jamming and detail the implementation on a quadruped robotic platform. The mechanism is inspired by the stiffness varying function of the tarsal bones in a human foot, and our aim is to understand how the change of foot stiffness can be used to improve the locomotion performance of legged robots. Using the same open loop trot gait in all experiments, it is shown that a fast state transition enables the robot to profit from both states, leading to more uniform foot placement patterns also on rough terrain compared to other tested feet. This results in overall faster gaits and even enables the robot to climb steeper inclined surfaces. GRAPHICAL ABSTRACT: